2017
DOI: 10.1039/c7dt00447h
|View full text |Cite
|
Sign up to set email alerts
|

Radical cations of phenyl silatrane

Abstract: Electrochemical oxidation of phenylsilatrane (1) in CHCN/0.1 M BuNPF has been studied by voltammetry, UV-Vis and EPR-coupled spectroelectrochemistry supported by DFT calculations. One-electron withdrawal from the HOMO of 1, formed with a predominant contribution of the atrane N atom to the 3c-4e system, results in a short lived radical cation, in which the atrane nitrogen atom is almost planar and carries most of the spin density showing strong coupling with the protons of the axially directed C-H bonds of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…10a Studies of the electron transfer aspect of this hyperbond are only at the very beginning, yet already opening many promising features. We have recently shown that when a metallatrane carries a relatively hard to ionize 1-substituent, electron withdrawal upon oxidation can directly affect this hyperbond, resulting in persistent cation radicals [10][11][12] with the spin localized inside the atrane cage on a practically planar N atom. 10c,12 Such systems show a great promise for various modern applications, primarily for spin-commutating interfaces 13 and as potential electromechanical actuators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10a Studies of the electron transfer aspect of this hyperbond are only at the very beginning, yet already opening many promising features. We have recently shown that when a metallatrane carries a relatively hard to ionize 1-substituent, electron withdrawal upon oxidation can directly affect this hyperbond, resulting in persistent cation radicals [10][11][12] with the spin localized inside the atrane cage on a practically planar N atom. 10c,12 Such systems show a great promise for various modern applications, primarily for spin-commutating interfaces 13 and as potential electromechanical actuators.…”
mentioning
confidence: 99%
“…10c,12 Such systems show a great promise for various modern applications, primarily for spin-commutating interfaces 13 and as potential electromechanical actuators. 11,12,14 Driven by the double interest for these compounds and continuing the works on the redox chemistry of intramolecular-coordinated derivatives of the elements of group 14 with pending 15 or included into a rigid structure 10, 11,16 coordinating groups, we envisaged a novel bis-metallatrane system with two fused atrane cages sharing a common nitrogen atom to form a 5c-6e hyperbond capped with two thienyl end-substituents (Scheme 1).…”
mentioning
confidence: 99%
“…When the reduction peaks of CRs appeared at v ∼ = 0.1 V s −1 (kinetic parameter λ = kRT/nFv falling in the interval 4 × 10 −3 < λ < 20 [27]), the k of deprotonation was directly derived using Equation (11) [38]: E p = E 0 + 0.78RT/nF − (RT/2nF)ln(λ) (11) When the i p a /i p c ratio in CV fell in the range between 0.25 (1d) and 0.59 (1h) at 1 V s −1 , the rate constant k was determined using the working curve i p a /i p c − log(kτ) (τ is the time elapsed during the scan between E 1/2 and the vertex potential) [36]. For ill-shaped CV peaks, when measuring the E p is difficult, the derived CV (DCV [27]) and two-step potentiostatic chronoamperometry (CA [36]) were used to assess k using inflection potential E i for E p/2 and peak current i [65].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the length of the N→Si contact in the atrane cage (l Si-N ) is directly related to the degree of the involvement of the nitrogen lone pair in the 3c-4e system, and hence to the ease of electron withdrawal (IP and HOMO level). Therefore, the variation of l Si-N caused by the oxidation (destroying the N→Si coordination in 1 +• [11]), i.e., ∆l = l Si-N (1 +• ) − l Si-N (1) (Table 2) is expected to correlate with the reorganization energy of the atrane carcass (λ i ), and further with k s . Then, shifting the process to the zone of ET control (v > 1-2 V s −1 , the rising parts of the ∆E p /∆lg(v) plots (see, e.g., Figure 1B) makes it possible to derive ∆G 0 = from the slope α/E p [38] and to consider the variation in the ET rate k s with the structural changes (l Si-N ) during the oxidation of silatranes.…”
Section: Electrochemistry Formation Of Crsmentioning
confidence: 99%
See 1 more Smart Citation